A Web-based Mobile Medical Monitoring System - Pollard , John K.; Rohman , S.; Fry , M. E. (International Journal of Computing, 2002)
A hospitalwide mobile medical monitoring system is described. Telemetry devices are attached to patients to acquire, store and process continuous data about their state of health. Medical staff may examine realtime graphical information and make comparisons with historical data. Parameters may be set to cause an automatic alert to portable devices held by appropriate staff if a patient requires urgent observation. The system uses the services provided by Internet and Intranet to allow remote supervision and consultation. A hardware/software prototype has been constructed to demonstrate realtime data acquisition, wireless transmission/reception and connection to the Worldwide Web. The realtime, supervisory and remote teaching aspects of the software system are being designed and are in the process of implementation.